PERANAN SAFETY MEETING DALAM MENINGKATKAN KESELAMATAN KERJA ABK DI KM. KENDHAGA NUSANTARA 6 - Muhammad Fikri Ramadhan; Eva Susanti; Ika Mustika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The objective of this study is to examine the role of safety meetings in enhancing the use of personal protective equipment (PPE) for crew occupational safety aboard KM. Kendhaga Nusantara 6. The research was conducted during the author’s sea practice using a qualitative approach. Primary data were collected through direct observation, in-depth interviews with the Chief Officer, Bosun, and Helmsmen, as well as documentation. Data analysis employed NVivo 12 Pro software following the Miles and Huberman model, which includes data reduction, presentation, and conclusion drawing. Findings reveal that the infrequent implementation of safety meetings—due to the absence of a fixed schedule, operational time constraints, and crew fatigue—was a major factor behind low PPE compliance. Several incidents highlighted this issue, such as crew members working without safety shoes and masks during brushing, resulting in injuries, and a Bosun working on scaffolding without a safety harness. Post-meeting evaluations, conducted through attendance monitoring and observation of workplace behavior, demonstrated that safety meetings held regularly, led by authorized officers, and supported by relevant materials with a positive approach, significantly improved PPE usage. Moreover, these meetings contributed to fostering a stronger safety culture aboard the vessel, encouraging discipline and responsibility among crew members.